2018
DOI: 10.1017/ihs.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

‘He came to her bed pretending courtship’: sex, courtship and the making of marriage in Ulster, 1750–1844

Abstract: The history of sex and sexuality is underdeveloped in Irish historical studies, particularly for the period before the late-nineteenth century. While much has been written on rates of illegitimacy in Ireland, and its regional diversity, little research has been conducted on how ordinary women and men viewed sex and sexuality. Moreover, we still know little about the roles that sex played in the rituals of courtship and marriage. Drawing on a sample of Presbyterian church records, this article offers some new i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…As O'Dowd has argued, while a 'plurality of masculinities' existed at any one time in early modern Ireland, 'across the ethnic divide, [men] demonstrated their belief that one of their main responsibilities was the care of their family'. 103 Presbyterian sources present further evidence of similarities across the confessional divide than differences.…”
Section: Men's Strategies To Recover and Restore Reputationmentioning
confidence: 92%
See 2 more Smart Citations
“…As O'Dowd has argued, while a 'plurality of masculinities' existed at any one time in early modern Ireland, 'across the ethnic divide, [men] demonstrated their belief that one of their main responsibilities was the care of their family'. 103 Presbyterian sources present further evidence of similarities across the confessional divide than differences.…”
Section: Men's Strategies To Recover and Restore Reputationmentioning
confidence: 92%
“…Recent scholarship has significantly challenged and revised these assumptions. 23 In common with the work of Mary O'Dowd and Maria Luddy, my own research has demonstrated how Presbyterian sources offer fresh perspectives on the wider Irish evidence, enriching our knowledge of many aspects of family life, including marriage, childbirth, sexuality and the law. 24 This article extends these conclusions and demonstrates how Presbyterian sources provide an alternative and unique insight into the sexual worlds of men in eighteenth-and nineteenth-century Ireland.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…50 Their work highlights how marital sexual experiences has been a largely neglected topic particularly from the mid nineteenth century, given recent work by Leanne Calvert on the eighteenth and early nineteenth centuries. 51 Analyses of sources that depict deviant or criminal sexual behaviour also reveal the corollary of what was considered 'normal'. The more 'common' female sexual experiences are revealed through scholarship on family planning or birth control.…”
Section: IIImentioning
confidence: 99%